2006
DOI: 10.1016/j.carbon.2006.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Titanium carbide derived nanoporous carbon for energy-related applications

Abstract: High surface area nanoporous carbon has been prepared by thermo-chemical etching of titanium carbide TiC in chlorine in the temperature range 200-1200 °C. Structural analysis showed that this carbide-derived carbon (CDC) was highly disordered at all synthesis temperatures. Higher temperature resulted in increasing ordering and formation of bent graphene sheets or thin graphitic ribbons. Soft X-ray absorption near-edge structure spectroscopy demonstrated that CDC consisted mostly of sp 2 bonded carbon. Small-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
290
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(314 citation statements)
references
References 23 publications
22
290
1
1
Order By: Relevance
“…Material synthesis: We synthesized CDC from commercially available powders of B 4 C, [17] ZrC, [18] TiC, [20] and SiC [19] at various temperatures in the 400-1200°C range. TiC, ZrC and B 4 C with the average particle size of ∼ 2-4 µm were obtained from Alfa Aesar, while β-SiC powder with the average particle size of ∼ 2 µm was obtained from Superior Graphite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Material synthesis: We synthesized CDC from commercially available powders of B 4 C, [17] ZrC, [18] TiC, [20] and SiC [19] at various temperatures in the 400-1200°C range. TiC, ZrC and B 4 C with the average particle size of ∼ 2-4 µm were obtained from Alfa Aesar, while β-SiC powder with the average particle size of ∼ 2 µm was obtained from Superior Graphite.…”
Section: Methodsmentioning
confidence: 99%
“…A gradual evolution of CDC structure as the chlorination temperature increases was revealed by Raman spectroscopy, X-Ray diffraction (XRD) [17][18][19][20] , and TEM (Fig. 4).…”
Section: Structure and Porositymentioning
confidence: 99%
“…Among the researches in EDLCs, it is an important field to develop electrode materials with large specific capacitance and high electrochemical stability [4]. Activated carbons (ACs) satisfy the basic requirements for the electrode materials of EDLCs due to its low cost, high surface area and large porosity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The pore size in these materials is highly influenced by the carbide precursor and reactive extraction temperature. Higher temperatures during synthesis may allow restructuring of the carbon to a higher degree of graphitization and larger pores are formed [6,15,16]. At lower synthesis temperatures carbon molecular sieves can result, which could be of interest for the application of gas separation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The pore structure can be further analyzed by small-angle scattering techniques like X-ray scattering (SAXS) or neutron scattering (SANS), which allows also probing closed pores. For titanium carbide-derived carbon (TiC-CDC), which is subject of this study, sorption isotherm analysis [16][17][18][19][20][21][22] and scattering [16,[23][24][25] results are discussed in literature, showing that TiC-CDC synthesized below 900 °C shows pore sizes in the range of carbon molecular sieves. Equilibrium CO 2 adsorption isotherms demonstrated that with TiC-CDC high CO 2 uptakes can be realized [26].…”
Section: Introductionmentioning
confidence: 99%